Peculiarities of the structural properties of InxGa1-xN polytype nanostructures grown by molecular-beam epitaxy. (March 2020) - Gridchin, V O; Kotlyar, K P; Reznik, R R; Shevchuk, D S; Kirilenko, D A; Bert, N A; Soshnikov, I P; Cirlin, G E
Abstract: In the article, the study of the morphology, crystal structure and chemical composition of Inx Ga1-x N nanostructures is presented. Scanning electron microscopy measurements show that the sample has a structure consisting of nanotubes, on top of which an array of nanocrystals (so-called "nanoflowers") is formed. The results of transmission electron microscopy show that the nanotubes have a wurtzite crystal structure, whereas the "nanoflowers" exhibit both wurtzite and zinc blende one. The indium composition in wurtzite and zinc blende segments is about 20 % and 10 %, respectively.